(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
Rivers in Jeli, Kelantan serve vital ecological, recreational, and socio-economic roles, yet their water quality faces growing threats from expanding tourism and associated land-use changes. This study aimed to assess the physicochemical and microbial quality of water in four major tourism rivers, Lata Janggut, Lata Keding, Lata Kashmir, and Lata Renyuk, by applying the Malaysian Department of Environment’s Water Quality Index (WQI) and quantifying Escherichia coli as an indicator of faecal contamination. In-situ and ex-situ analyses measured parameters including dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), ammoniacal nitrogen (NH?-N), total suspended solids (TSS), and pH. Results indicated that all sites exhibited WQI values within Class I and Class II, corresponding to excellent and good water quality suitable for recreation. However, E. coli enumeration revealed sporadic contamination events, suggesting intermittent faecal pollution likely linked to human and animal activities near the rivers. The findings underscore a potential disconnect between physicochemical water quality and microbial safety, highlighting the need for integrated monitoring approaches. This study provides new insights into the status and challenges of river water quality at rural tourism destinations in Malaysia, informing recommendations for targeted pollution control, enhanced public awareness, and sustainable river management to protect both public health and ecological integrity.